Cold bayou - Hambly, Barbara (Hambly, Barbara. Benjamin January series, 2018)
"New Orleans, 1839. Despite his misgivings, Benjamin January has agreed to play the piano at the wedding of wealthy French Creole landowner Veryl St-Chinian. All is not well, for the marriage of 67-year-old, profoundly infatuated Uncle Veryl to an 18-year-old Irish tavern-slut spells potential disaster for everyone in the inter-married Viellard and St-Chinian clans. But the old man is determined to marry Miss Ellie Trask, and nothing will stand in his way. On the isolated plantation of Cold Bayou where the ceremony is to take place, tension is rife even before the body is discovered in the woods behind the dower house, its throat cut. A yet more disturbing turn of events sees January himself accused of the crime."--Provided by publisher.